Evolving a Structural Model in Type 2 Diabetes Mellitus: Influence of Knowledge Attitudes, and Self-Management Practices on Glycaemic Control - Matpady Prabhath Kalkura; Shashikiran Umakanth; Arun Gundmi Maiya; Shreemathi Sureshramana Mayya; Krishnanda Prabhu Renjala Vasudeva; Mamatha Shivananda Pai; Pallavi Prakash Saraswat; Balkudru Kiran Aithal (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Regularity in diabetes self-management practices among people with Type 2 Diabetes Mellitus (T2DM) is a predictor of glycaemic control. Knowledge and attitude have linear relationships with diabetes self-management, and hence exert a positive influence on glycaemic control. Aim: The study aimed to develop and examine a structural model describing the inter-relationship between diabetes knowledge, attitude, self-management practices, and glycaemic control {demonstrated by glycated haemoglobin (HbA1c) levels}. Materials and Methods: A cross-sectional study was conducted among people with T2DM in Udupi taluk, Karnataka, India. A total of 432 participants, selected by simple random sampling and fulfilling the inclusion criteria, were included in the study. Descriptive, correlative and comparative analysis of data was done using Statistical Package for the Social Sciences (SPSS) version 16.0. The Structural Equation Modelling (SEM) technique was used for the model; and path analysis was performed using Analysis of Moment Structures (AMOS) version 25.0 software. Results: Diabetes knowledge was a significant predictor of attitude, which in turn were a significant predictor of diabetes self-management and HbA1c. Importantly, diabetes selfmanagement was a significant predictor for HbA1c. The final model reflected good fit (χ2 (5) =5.849, p=0.321, RMSEA= 0.019, CFI= 1, NFI=0.997). Conclusion: The present study strongly indicates that attitude and self-management practices can have a direct impact on HbA1c levels of people with T2DM. Knowledge has an indirect impact on self-management and HbA1c through attitude. Developing a self-management intervention model (which can be tailored to suit the needs of the individual with T2DM) encompassing knowledge, positive attitude and diabetes self-management practices, might result in improved glycaemic control among people with T2DM, and it will be more sustainable than other interventions since it would work at the community level.